Kikuchi-Fujimoto disease in fine needle aspiration smears: A clinico-cytologic study of 18 pediatric cases and correlation with 68 adult patients - Dilip K Das; Bahiya I Haji; Ruaá A.A Al-Boijan; Zafar A Sheikh; Shahed K Pathan; Abul A.S.R Mannan (Wolters Kluwer Medknow Publications, 2012)
Objective: Kikuchi-Fujimoto disease (KFD) is a self-limiting disorder which usually affects young women. There are only a few studies on pediatric KFD patients and their fine-needle aspiration (FNA) cytodiagnosis. We report a series of pediatric KFD patients diagnosed by FNA cytology and compare them with adults. Materials and Methods: By routine FNA cytology and through retrospective review smears initially diagnosed as reactive hyperplasia of lymph node during the years 2004-2009, 18 pediatric and 68 adult KFD cases were detected. The clinico-cytologic features of these two groups were compared. Results: The age of the pediatric patients ranged from 6 to 18 years with a median of 13.5 years and adult cases were aged 19 to 54 years with a median of 30 years. Only 1 pediatric case (5.6%) and 20 (29.4%) adult cases were initially diagnosed as KFD (P = 0.0604). Arab:non-Arab ratios were 4.3:1 among the pediatric patients and 1:1.5 for the adults (P = 0.0043). FNA smears were highly cellular in 4 (22.2%) pediatric cases and 37 (54.4%) adult cases (P = 0.0180). More than 5% Kikuchi histiocytes was present in 8 (44.4%) pediatric and 49 (72.1%) adult cases (P = 0.0474). No significant difference was observed in male: female ratio, frequency of head & neck lymphadenopathy, time (season) of presentation, and presence of neutrophils and capillary networks, etc. Conclusions: Besides observation and interpretation errors, a significant difference between the two groups in respect of some clinico-cytomorphological features could have influenced the routine cytodiagnosis leading to lower pickup rate of pediatric KFD cases as compared to adults.